El mindfulness y su eficacia en adultos en duelo - Aranda Castillo, Maria Fe (2021)
The constant increase in deaths due to COVID-19 supposes greater cases of bereavement, so it is considered necessary to provide effective interventions for its optimal approach and prevent health consequences. The present work aimed to identify the efficacy of Mindfulness interventions in adults who are going through a grieving process. For this, a review study of primary research was carried out that evaluated the issue raised using certain criteria of the PRISMA guide (Urrútia & Bonfill, 2010) and consulting the following databases: Ebsco, Proquest, Science Direct and Scopus. In order to define the analysis, 7 representative works were selected. The results show that Mindfulness interventions in grieving adults reduce dysfunctional symptoms such as anxiety, anguish and elevated depression and increase mindfulness itself. Although current research on this problem is scarce, the importance of using integrative and effective approaches such as Mindfulness that allow functional emotional management, especially in high-impact contexts such as a pandemic, is presented. For future research, it is recommended to improve and expand the studies in terms of both variables with higher quality procedures and methodological rigor.